The Effect of Diet on the Cardiac Circadian Clock in Mice: A Systematic Review - Ana Beatriz Rezende Paula; Letícia Teresinha Resende; Isabela Alcântara Barretto Araújo Jardim; Bianca Iara Campos Coelho; Denise de Coutinho Miranda; Alexandre Martins Oliveira Portes; Maria Cecília Teles; Ana Maria de Lauro Castrucci; Mauro César Isoldi (Metabolites, 2022)
Circadian rhythms play important roles in regulating physiological and behavioral processes. These are adjusted by environmental cues, such as diet, which acts by synchronizing or attenuating the circadian rhythms of peripheral clocks, such as the liver, intestine, pancreas, white and brown adipose tissue, lungs, kidneys, as well as the heart. Some studies point to the influence of diet composition, feeding timing, and dietary restriction on metabolic homeostasis and circadian rhythms at various levels. Therefore, this systematic review aimed to discuss studies addressing the effect of diet on the heart clock in animal models and, additionally, the chronodisruption of the clock and its relation to the development of cardiovascular disorders in the last 15 years. A search was conducted in the PubMed, Scopus, and Embase databases. The PRISMA guide was used to construct the article. Nineteen studies met all inclusion and exclusion criteria. In summary, these studies have linked the circadian clock to cardiovascular health and suggested that maintaining a robust circadian system may reduce the risks of cardiometabolic and cardiovascular diseases. The effect of time-of-day-dependent eating on the modulation of circadian rhythms of the cardiac clock and energy homeostasis is notable, among its deleterious effects predominantly in the sleep (light) phase and/or at the end of the active phase.